INVESTIGATION OF THE EFFECTS OF AGING ON PHASE TRANSFORMATION OF Cu-Al-Mn SHAPE MEMORY ALLOYS - Ozkul, I.; Aldas, K.; Canbay, C. Aksu (Scibulcom Ltd, 2015)
In this study, the aging effects were investigated on four different Cu-Al-Mn alloys. During the experiments, three different temperature values and three different time intervals were selected and experiments were conducted at muffle furnace with 40 sets specimens. The phase transform temperatures have been detected by differential scanning calorimetry. The results indicated that the values of transformation temperatures increased due to the increasing the values of aging temperatures generally. In addition nonsequential transition temperatures were observed regarding experiment conditions depend on pinning effects during aging.
Keywords: shape memory; aging; Cu-Al-Mn; DSC